Propuesta de un plan basado en Lean Six Sigma para mejorar la eficiencia del area logística de la empresa minera La Arena S.A. - año 2016 - Cueva Vigo, Fermín (2016)
This research aims to determine whether there is a direct relationship between a new proposal based on Lean Six Sigma to improve efficiency of Logistics area Empresa Minera S.A. Arena Plan - 2016. The research problem is referred to the following question: How does a system based on Lean Six Sigma to improve the efficiency of the logistics of the mining company plan Arena S.A. - Year 2016 ?, whose hypothesis is based on Lean Six Sigma Plan favorably influences the efficiency of the logistics in the mining company La Arena SA - Year 2016, highlighting as study variables: Independent Variable: Lean Six Sigma Plan; and the dependent variable: Logistics Area. design was used descriptive investigation and inductive methods; analytical, statistical and technical research data collection, as the survey. Through studies conducted in the company of Minera La Arena SA in the area of logistics it can be concluded that: The procurement and supply at a reasonable percentage of companies are deficient because they fail to clearly identify the processes and uses improvisation users causing unnecessary reporting requirements without negatively affecting the livelihood profitability. Logistics management in a reasonable percentage does not include processes and operations necessary to provide the consumer the right product in the right quantity required and what makes significant influence on the financial performance conditions. In this thesis, the activities of procurement management was analyzed and plotted graphically, these results were the basis for the formulation of strategies for the new proposal. In addition to formulating conclusions and recommendations of this research.